miR-15/107 microRNA Gene Group: Characteristics and Functional Implications in Cancer - Turco, Chiara; Donzelli, Sara; Fontemaggi, Giulia (Frontiers in Cell and Developmental Biology, 2020)
miR-15/107 group of microRNAs (miRNAs) encloses 10 annotated human members and is defined based on the presence of the sequence AGCAGC near the mature miRNAs' 5’ end. Members of miR-15/107 group expressed in humans are highly evolutionarily conserved and seven of these miRNAs are widespread in vertebrate species. Contrarily to the majority of miRNAs which recognize complementary sequences on the 3’UTR region, some members of the miR-15/107 group are peculiarly characterized by the ability to target the coding sequence (CDS) of their target mRNAs, inhibiting translation without strongly affecting their mRNA levels. There is compelling evidence that different members of the miR-15/107 group regulate overlapping lists of mRNA targets but also show target specificity. The ubiquitously expressed miR-15/107 gene group controls several human cellular pathways, such as proliferation, angiogenesis and lipid metabolism, and might be altered in various diseases, such as neurodegenerative diseases and cancer. Intriguingly, despite they share the same seed sequence different members of this family of miRNAs may behave as oncomiRs or as tumor suppressor miRNAs in the context of cancer cells. This review discusses the regulation and functional contribution of miR-15/107 group to the control of gene expression. Moreover, we particularly focus on the contribution of specific miR-15/107 group members as tumor suppressors in breast cancer, reviewing literature reporting their ability to function as major controllers of a variety of cell pathways and to act as powerful biomarkers in this disease.